Microarchitectural Vulnerabilities Introduced, Exploited, and Accelerated by Heterogeneous FPGA-CPU Platforms - Tiemann, Thore; Weissman, Zane; Eisenbarth, Thomas; Sunar, Berk (Security of FPGA-Accelerated Cloud Computing Environments, 2024)

PrivAgE: A Toolchain for Privacy-Preserving Distributed Aggregation on Edge-Devices - Liebenow, Johannes; Imort, Timothy; Fuchs, Yannick; Heisel, Marcel; K{ading, Nadja; Rupp, Jan; Mohammadi, Esfandiar (KI - K{unstliche Intelligenz, 2024)

SEV-Step: A Single-Stepping Framework for AMD-SEV - Wilke, Luca; Wichelmann, Jan; Rabich, Anja; Eisenbarth, Thomas (IACR Transactions on Cryptographic Hardware and Embedded Systems (TCHES), 2024)

OBELIX: Mitigating Side-Channels Through Dynamic Obfuscation - Wichelmann, Jan; Rabich, Anja; P{atschke, Anna; Eisenbarth, Thomas (2024 IEEE Symposium on Security and Privacy (SP), 2024)

TeeJam: Sub-Cache-Line Leakages Strike Back - Sieck, Florian; Zhang, Zhiyuan; Berndt, Sebastian; Chuengsatiansup, Chitchanok; Eisenbarth, Thomas; Yarom, Yuval (IACR Transactions on Cryptographic Hardware and Embedded Systems (TCHES), 2023)

SystemC Model of Power Side-Channel Attacks Against AI Accelerators: Superstition or not? - Neskovic, Andrija; Mulhem, Saleh; Treff, Alexander; Buchty, Rainer; Eisenbarth, Thomas; Berekovic, Mladen (ICCAD '23: Proceedings of the 42nd IEEE/ACM International Conference on Computer-Aided Design, 2023)

S-GBDT: Frugal Differentially Private Gradient Boosting Decision Trees - Kirschte, Moritz; Peinemann, Thorsten; Stock, Joshua; Cotrini, Carlos; Mohammadi, Esfandiar (arXiv, 2023)

Okapi: A Lightweight Architecture for Secure Speculation Exploiting Locality of Memory Accesses - Schmitz, Philipp; Jauch, Tobias; Wezel, Alex; Fadiheh, Mohammad R.; Tiemann, Thore; Heller, Jonah; Eisenbarth, Thomas; Stoffel, Dominik; Kunz, Wolfgang (2023)

Overcoming the Pitfalls of HPC-based Cryptojacking Detection in Presence of GPUs - Pott, Claudius; Gulmezoglu, Berk; Eisenbarth, Thomas (Proceedings of the Thirteenth ACM Conference on Data and Application Security and Privacy, CODASPY 2023, Charlotte, NC, USA, April 24-26, 2023, 2023)

Subversion-Resilient Authenticated Encryption Without Random Oracles - Bemmann, Pascal; Berndt, Sebastian; Diemert, Denis; Eisenbarth, Thomas; Jager, Tibor (Applied Cryptography and Network Security - 21st International Conference, ACNS 2023, Kyoto, Japan, June 19-22, 2023, Proceedings, Part II, 2023)

MAMBO-V: Dynamic Side-Channel Leakage Analysis on RISC-V - Wichelmann, Jan; Peredy, Christopher; Sieck, Florian; P{atschke, Anna; Eisenbarth, Thomas (Detection of Intrusions and Malware, and Vulnerability Assessment (DIMVA) - 20th International Conference, 2023)

Madvex: Instrumentation-based Adversarial Attacks on Machine Learning Malware Detection - Loose, Nils; M{achtle, Felix; Pott, Claudius; Bezsmertnyi, Volodymyr; Eisenbarth, Thomas (Detection of Intrusions and Malware, and Vulnerability Assessment (DIMVA) - 20th International Conference, 2023)

IOTLB-SC: An Accelerator-Independent Leakage Source in Modern Cloud Systems - Tiemann, Thore; Weissman, Zane; Eisenbarth, Thomas; Sunar, Berk (Proceedings of the 2023 ACM Asia Conference on Computer and Communications Security, 2023)

DPM: Clustering Sensitive Data through Separation - Sch{utt, Yara; Liebenow, Johannes; Braun, Tanya; Gehrke, Marcel; Thaeter, Florian; Mohammadi, Esfandiar (CoRR, 2023)

Act natural!: Exchanging Private Messages on Public Blockchains - Tiemann, Thore; Berndt, Sebastian; Eisenbarth, Thomas; Liskiewicz, Maciej (8th IEEE European Symposium on Security and Privacy, 2023)

Combined Fault and Leakage Resilience: Composability, Constructions and Compiler - Berndt, Sebastian; Eisenbarth, Thomas; Faust, Sebastian; Gourjon, Marc; Orlt, Maximilian; Seker, Okan (Advances in Cryptology - CRYPTO 2023 - 43rd Annual International Cryptology Conference, CRYPTO 2023, Santa Barbara, CA, USA, August 20-24, 2023, Proceedings, Part III, 2023)
Real-world cryptographic implementations nowadays are not only attacked via classical cryptanalysis but also via implementation attacks, including passive attacks (observing side-channel information about the inner computation) and active attacks (inserting faults into the computation). While countermeasures exist for each type of attack, countermeasures against combined attacks have only been considered recently. Masking is a standard technique for protecting against passive side-channel attacks, but protecting against active attacks with additive masking is challenging. Previous approaches include running multiple copies of a masked computation, requiring a large amount of randomness or being vulnerable to horizontal attacks. An alternative approach is polynomial masking, which is inherently fault-resistant.
://eprint.iacr.org/2023/1143

Cipherfix: Mitigating Ciphertext Side-Channel Attacks in Software - Wichelmann, Jan; P{atschke, Anna; Wilke, Luca; Eisenbarth, Thomas (32nd USENIX Security Symposium, USENIX Security 2023, Anaheim, CA, USA, August 9-11, 2023, 2023)

Distributed DP-Helmet: Scalable Differentially Private Non-interactive Averaging of Single Layers - Kirschte, Moritz; Meiser, Sebastian; Ardalan, Saman; Mohammadi, Esfandiar (arXiv, 2022)

ASAP: Algorithm Substitution Attacks on Cryptographic Protocols - Berndt, Sebastian; Wichelmann, Jan; Pott, Claudius; Traving, Tim-Henrik; Eisenbarth, Thomas (Proceedings of the 2022 ACM Asia Conference on Computer and Communications Security, 2022)
Keywords: security protocols signal subversion attacks tls wireguard

A Systematic Look at Ciphertext Side Channels on AMD SEV-SNP - Li, Mengyuan; Wilke, Luca; Wichelmann, Jan; Eisenbarth, Thomas; Teodorescu, Radu; Zhang, Yinqian (2022 IEEE Symposium on Security and Privacy (SP), 2022)

Microwalk-CI: Practical Side-Channel Analysis for JavaScript Applications - Wichelmann, Jan; Sieck, Florian; P{atschke, Anna; Eisenbarth, Thomas (Proceedings of the 2022 ACM SIGSAC Conference on Computer and Communications Security, CCS 2022, Los Angeles, CA, USA, November 7-11, 2022, 2022)

Util: : Lookup: Exploiting Key Decoding in Cryptographic Libraries - Sieck, Florian; Berndt, Sebastian; Wichelmann, Jan; Eisenbarth, Thomas (CCS '21: 2021 ACM SIGSAC Conference on Computer and Communications Security, 2021)

undeSErVed trust: Exploiting Permutation-Agnostic Remote Attestation - Wilke, Luca; Wichelmann, Jan; Sieck, Florian; Eisenbarth, Thomas (2021 IEEE Security and Privacy Workshops (SPW), 2021)

Nano Security: From Nano-Electronics to Secure Systems - Polian, Ilia; Altmann, Frank; Arul, Tolga; Boit, Christian; Brederlow, Ralf; Davi, Lucas; Drechsler, Rolf; Du, Nan; Eisenbarth, Thomas; G{uneysu, Tim; Hermann, Sascha; Hiller, Matthias; et al. (Design, Automation & Test in Europe Conference & Exhibition, DATE 2021, Grenoble, France, February 1-5, 2021, 2021)

Side-Channel Protections for Picnic Signatures - Aranha, Diego F.; Berndt, Sebastian; Eisenbarth, Thomas; Seker, Okan; Takahashi, Akira; Wilke, Luca; Zaverucha, Greg (IACR Transactions on Cryptographic Hardware and Embedded Systems, 2021)

Robust Online Algorithms for Dynamic Choosing Problems - Berndt, Sebastian; Grage, Kilian; Jansen, Klaus; Johannsen, Lukas; Kosche, Maria (Connecting with Computability - 17th Conference on Computability in Europe, CiE 2021, Virtual Event, Ghent, July 5-9, 2021, Proceedings, 2021)

Responsible and Regulatory Conform Machine Learning for Medicine: A Survey of Technical Challenges and Solutions - Petersen, Eike; Potdevin, Yannik; Mohammadi, Esfandiar; Zidowitz, Stephan; Breyer, Sabrina; Nowotka, Dirk; Henn, Sandra; Pechmann, Ludwig; Leucker, Martin; Rostalski, Philipp; Herzog, Christian (CoRR, 2021)

New Bounds for the Vertices of the Integer Hull - Berndt, Sebastian; Jansen, Klaus; Klein, Kim-Manuel (4th Symposium on Simplicity in Algorithms, SOSA 2021, Virtual Conference, January 11-12, 2021, 2021)

Tightness of Sensitivity and Proximity Bounds for Integer Linear Programs - Berndt, Sebastian; Jansen, Klaus; Lassota, Alexandra (SOFSEM 2021: Theory and Practice of Computer Science - 47th International Conference on Current Trends in Theory and Practice of Computer Science, SOFSEM 2021, Bolzano-Bozen, Italy, January 25-29, 2021, Proceedings, 2021)

Load Balancing: The Long Road from Theory to Practice - Berndt, Sebastian; Deppert, Max A.; Jansen, Klaus; Rohwedder, Lars (CoRR, 2021)

Help, My Signal has Bad Device! - Breaking the Signal Messenger's Post-Compromise Security Through a Malicious Device - Wichelmann, Jan; Berndt, Sebastian; Pott, Claudius; Eisenbarth, Thomas (Detection of Intrusions and Malware, and Vulnerability Assessment - 18th International Conference, DIMVA 2021, Virtual Event, July 14-16, 2021, Proceedings, 2021)

Firmware Security Module: A Framework for Trusted Computing in Automotive Multiprocessors - Pott, Claudius; Jungklass, Philipp; Csejka, David Jacek; Eisenbarth, Thomas; Siebert, Marco (Journal of Hardware and Systems Security, 2021)
New services such as autonomous driving, the connectivity of the traffic infrastructure and the tight coupling of user operated smart devices with the vehicle have significantly increased the demand for cryptographic protection in the automobile. To provide a secure environment for the calculation and verification of cryptographic material, automotive microcontrollers now frequently integrate Hardware Security Modules (HSM), special well-protected co-processors, which are protected against manipulation and external access. HSMs use special hardware accelerators to provide the required cryptographic services. While these accelerators provide good performance, they limit flexibility and updatability. In addition, as more services require cryptographic protection, the amount of key material that needs to be managed by the HSM also increases, turning the limited protected memory of the HSM into a bottleneck. This paper presents a framework that uses the safety mechanisms of a microcontroller to achieve both HSM-equivalent security through software solutions, while providing an equivalent level of functionality. Furthermore, the proposed framework provides crypto-agility, as the security stack can be updated if desired. In order to verify the functionality, the presented framework is implemented and evaluated on an Infineon AURIX TC399 and compared with the integrated HSM.

Divide and Funnel: a Scaling Technique for Mix-Networks - Das, Debajyoti; Meiser, Sebastian; Mohammadi, Esfandiar; Kate, Aniket (IACR Cryptol. ePrint Arch., 2021)

Differential Power Analysis of the Picnic Signature Scheme - Gellersen, Tim; Seker, Okan; Eisenbarth, Thomas (Post-Quantum Cryptography - 12th International Workshop, PQCrypto 2021, Daejeon, South Korea, July 20-22, 2021, Proceedings, 2021)

Aim, Wait, Shoot: How the CacheSniper Technique Improves Unprivileged Cache Attacks - Briongos, Samira; Bruhns, Ida; Malag'on, Pedro; Eisenbarth, Thomas; Moya, Jos'e Manuel (IEEE European Symposium on Security and Privacy, EuroS &P 2021, Vienna, Austria, September 6-10, 2021, 2021)

A White-Box Masking Scheme Resisting Computational and Algebraic Attacks - Seker, Okan; Eisenbarth, Thomas; Liskiewicz, Maciej (IACR Transactions on Cryptographic Hardware and Embedded Systems, 2021)
://eprint.iacr.org/2020/443

A Formal Approach to Confidentiality Verification in SoCs at the Register Transfer Level - M{uller, Johannes; Fadiheh, Mohammad Rahmani; Duque Ant'on, Anna Lena; Eisenbarth, Thomas; Stoffel, Dominik; Kunz, Wolfgang (58th ACM/IEEE Design Automation Conference, DAC 2021, San Francisco, CA, USA, December 5-9, 2021, 2021)

Learning Numeric Optimal Differentially Private Truncated Additive Mechanisms - Sommer, David M.; Abfalterer, Lukas; Zingg, Sheila; Mohammadi, Esfandiar (CoRR, 2021)

RELOAD+REFRESH: Abusing Cache Replacement Policies to Perform Stealthy Cache Attacks - Briongos, Samira; Malagon, Pedro; Moya, Jose M.; Eisenbarth, Thomas (29th USENIX Security Symposium (USENIX Security 20), 2020)

TPM-FAIL: TPM meets Timing and Lattice Attacks - Moghimi, Daniel; Sunar, Berk; Eisenbarth, Thomas; Heninger, Nadia (29th USENIX Security Symposium (USENIX Security 20), 2020)

Solving Packing Problems with Few Small Items Using Rainbow Matchings - Bannach, Max; Berndt, Sebastian; Maack, Marten; Mnich, Matthias; Lassota, Alexandra; Rau, Malin; Skambath, Malte (MFCS 2020, 2020)

SNI-in-the-head: Protecting MPC-in-the-head Protocols against Side-channel Analysis - Seker, Okan; Berndt, Sebastian; Wilke, Luca; Eisenbarth, Thomas (CCS '20: 2020 ACM SIGSAC Conference on Computer and Communications Security, 2020)

SEVurity: No Security Without Integrity - Breaking Integrity-Free Memory Encryption with Minimal Assumptions - Wilke, Luca; Wichelmann, Jan; Morbitzer, Mathias; Eisenbarth, Thomas (2020 IEEE Symposium on Security and Privacy (SP), 2020)
Keywords: application-security; attacks-and-defenses; cloud-security; network-and-systems-security; security-architectures; trustworthy-computing

Microarchitectural Isolation Guarantees Through Execution Based Signatures - Briongos, Samira; Malag'on, Pedro; Moya, Jose Manuel; Eisenbarth, Thomas (XXXV Conference on Design of Circuits and Integrated Systems, DCIS, 2020, Segovia, Spain, November 18-20, 2020, 2020)

PACE Solver Description: PID (star) - Bannach, Max; Berndt, Sebastian; Schuster, Martin; Wien{obst, Marcel (IPEC, 2020)

PACE Solver Description: Fluid - Bannach, Max; Berndt, Sebastian; Schuster, Martin; Wien{obst, Marcel (IPEC, 2020)

On the universal steganography of optimal rate - Berndt, Sebastian; Liskiewicz, Maciej (Inf. Comput., 2020)

JackHammer: Efficient Rowhammer on Heterogeneous FPGA-CPU Platforms - Weissman, Zane; Tiemann, Thore; Moghimi, Daniel; Custodio, Evan; Eisenbarth, Thomas; Sunar, Berk (IACR Transactions on Cryptographic Hardware and Embedded Systems, 2020)

Comprehensive Anonymity Trilemma: User Coordination is not enough - Das, Debajyoti; Meiser, Sebastian; Mohammadi, Esfandiar; Kate, Aniket (Proceedings on Privacy Enhancing Technologies (PETS/PoPETS) 2020.3, 2020)

SPOILER: Speculative Load Hazards Boost Rowhammer and Cache Attacks - Islam, Saad; Moghimi, Ahmad; Bruhns, Ida; Krebbel, Moritz; Gulmezoglu, Berk; Eisenbarth, Thomas; Sunar, Berk (28th USENIX Security Symposium (USENIX Security 19), 2019)

Undermining User Privacy on Mobile Devices Using AI - Gulmezoglu, Berk; Zankl, Andreas; Tol, M. Caner; Islam, Saad; Eisenbarth, Thomas; Sunar, Berk (Proceedings of the 2019 ACM Asia Conference on Computer and Communications Security, 2019)
Keywords: activity inference; arm; artificial intelligence; cache attack; machine learning; microarchitecture; mobile device; user privacy

Deniable Upload and Download via Passive Participation - Sommer, David; Dhar, Aritra; Malisa, Luka; Mohammadi, Esfandiar; Ronzani, Daniel; Capkun, Srdjan (16th USENIX Symposium on Networked Systems Design and Implementation (NSDI 19), 2019)

Privacy Loss Classes: The Central Limit Theorem in Differential Privacy - Sommer, David; Meiser, Sebastian; Mohammadi, Esfandiar (Proceedings on Privacy Enhancing Technologies, 2019)

FortuneTeller: Predicting Microarchitectural Attacks via Unsupervised Deep Learning - Gulmezoglu, Berk; Moghimi, Ahmad; Eisenbarth, Thomas; Sunar, Berk (arXiv e-prints, 2019)
Keywords: Computer Science - Cryptography and Security; Computer Science - Machine Learning

Passive and active attackers in noiseless privacy - Desfontaines, Damien; Krahmer, Elisabeth; Mohammadi, Esfandiar (CoRR, 2019)

MemJam: A False Dependency Attack Against Constant-Time Crypto Implementations - Moghimi, Ahmad; Wichelmann, Jan; Eisenbarth, Thomas; Sunar, Berk (International Journal of Parallel Programming, 2018)

IT Security in L{ubeck - The design of a modern and future-proof security curriculum - Stelzner, Marc; Eisenbarth, Thomas (2018 12th European Workshop on Microelectronics Education (EWME), 2018)
Keywords: computer science education; educational courses; further education; security of data; University of L{ubeck; computer scientist training; IT security; degree program; design principle; well trained security professionals; dependable systems; digitally connected systems; future-proof security curriculum; Computer science; Education; Hardware; Computer security; Software reliability; IT Security; degree program; bachelor; master; education; security by design

MicroWalk: A Framework for Finding Side Channels in Binaries - Wichelmann, Jan; Moghimi, Ahmad; Eisenbarth, Thomas; Sunar, Berk (Proceedings of the 34th Annual Computer Security Applications Conference, 2018)

MASCAT: Preventing Microarchitectural Attacks Before Distribution - Irazoqui, Gorka; Eisenbarth, Thomas; Sunar, Berk (Proceedings of the Eighth ACM Conference on Data and Application Security and Privacy, CODASPY 2018, Tempe, AZ, USA, March 19-21, 2018, 2018)

Identifying and Eliminating Side-Channel Leaks in Programmable Systems - De Mulder, Elke; Eisenbarth, Thomas; Schaumont, Patrick (IEEE Design Test, 2018)
Keywords: security of data; side-channel leaks identification; side-channel leaks elimination; programmable systems; Threshold current; Power system reliability; Power distribution; Side-channel attacks; Microprocessors; Side-channel Leakage; Side-channel Analysis; Differential Power Analysis; Side-channel Countermeasures; Hiding; Masking; Threshold Implementation; Re-Keying; Side-channel Leakage Testing

Extending Glitch-Free Multiparty Protocols to Resist Fault Injection Attacks - Seker, Okan; Fernandez-Rubio, Abraham; Eisenbarth, Thomas; Steinwandt, Rainer (IACR Transactions on Cryptographic Hardware and Embedded Systems, 2018)

DeepCloak: Adversarial Crafting As a Defensive Measure to Cloak Processes - Inci, Mehmet Sinan; Eisenbarth, Thomas; Sunar, Berk (2018)

CacheShield: Detecting Cache Attacks through Self-Observation - Briongos, Samira; Irazoqui, Gorka; Malagon, Pedro; Eisenbarth, Thomas (Proceedings of the Eighth ACM Conference on Data and Application Security and Privacy, CODASPY 2018, Tempe, AZ, USA, March 19-21, 2018, 2018)

CacheQuote: Efficiently Recovering Long-term Secrets of SGX EPID via Cache Attacks - Dall, Fergus; Micheli, Gabrielle De; Eisenbarth, Thomas; Genkin, Daniel; Heninger, Nadia; Moghimi, Ahmad; Yarom, Yuval (IACR Trans. Cryptogr. Hardw. Embed. Syst., 2018)

CacheShield: Protecting Legacy Processes Against Cache Attacks - Briongos, Samira; Irazoqui, Gorka; Malagon, Pedro; Eisenbarth, Thomas (2017)

Cache-Based Application Detection in the Cloud Using Machine Learning - Gulmezoglu, Berk; Eisenbarth, Thomas; Sunar, Berk (Proceedings of the 2017 ACM on Asia Conference on Computer and Communications Security, 2017)
Keywords: SVM; cross-vm attacks; machine learning; prime{ & #38; probe

CacheZoom: How SGX Amplifies the Power of Cache Attacks - Moghimi, Ahmad; Irazoqui, Gorka; Eisenbarth, Thomas (Cryptographic Hardware and Embedded Systems - CHES 2017 - 19th International Conference, Taipei, Taiwan, September 25-28, 2017, Proceedings, 2017)

Did we learn from LLC Side Channel Attacks? A Cache Leakage Detection Tool for Crypto Libraries - Irazoqui, Gorka; Cong, Kai; Guo, Xiaofei; Khattri, Hareesh; Kanuparthi, Arun; Eisenbarth, Thomas; Sunar, Berk (CoRR, 2017)

PerfWeb: How to Violate Web Privacy with Hardware Performance Events - Gulmezoglu, Berk; Zankl, Andreas; Eisenbarth, Thomas; Sunar, Berk (Computer Security - ESORICS 2017 - 22nd European Symposium on Research in Computer Security, Oslo, Norway, September 11-15, 2017, Proceedings, Part II, 2017)

uLeech: A side-channel evaluation platform for IoT - Moukarzel, Michael; Eisenbarth, Thomas; Sunar, Berk (2017 IEEE 60th International Midwest Symposium on Circuits and Systems (MWSCAS), 2017)
Keywords: computer network security; cryptography; Internet; Internet of Things; microphones; next generation networks; security of data; smart phones; telecommunication security; wireless channels; side-channel evaluation platform; embedded trusted platform module; security critical applications; physical security analysis; IoT device; smart phone; ?Leech; next generation power scavenging devices; square point-of-sale reader; microphone-speaker interface; cryptographic services; power trace acquisition; clock manipulation attack; Capacitors; Cryptography; Resistors; Radiation detectors; Protocols; Resistance; Side-Channel; IoT; Low Power